Thermal evolution of a kaolin: Quantitative phase analysis and assessment of the thermal markers of the Provins clay - Wallez, Gilles; Bouquillon, Anne; Coquinot, Yvan (Applied clay science, 2024)
The thermal evolution of a kaolin from Provins, France, has been monitored using X-ray diffraction and Rietveld analysis over the 950–1200 °C range. The quantitative assessment of the evolution of mullite, cristobalite and the transient spinel was made possible by the recent resolution of the crystal structure of the latter phase, thus leading to investigate and explain its two-step nucleation mechanism. The progressive transformation of anatase (TiO2) into rutile was measured the same way, along with the mean crystallite size and cell parameters evolution of mullite. These transformations were then discussed in order to propose relevant thermal markers likely to be used to assess the thermal treatments undergone by kaolinite-based ceramics. In the present case, the rutile/anatase ratio turned to be relevant up to 1100 °C, mullite's a parameter in the domain of crystallization of primary mullite (950–1150 °C), while the mullite/spinel ratio and mullite crystallite size make reliable thermal markers in the domain of secondary mullite (1100–1200 °C), thus covering a wide range of temperature likely to be used in traditional earthenware making. •first global Rietveld analysis of a calcined kaolinic potter clay.•in-depth analysis of the Provins kaolin.•mechanism of the two-step nucleation of the transient spinel phase.•identification of relevant thermal markers for a posteriori assessment of thermal treatments.